Penerapan Model Pembelajaran Kooperatif Tipe Scramble Pada Pembelajaran IPA Fisika Peserta Didik Kelas VIII MTSS Nagari Gantung Ciri Kabupaten Solok - Armimitika, Armimitika (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This Research background of the lack of attention and student active in implementation of physics learning that still on teacher centerin MTsS of Gantung Ciri Solok regency. This problem can observeresult learning model thatgivea not effective, because the teacher oftenus group of student to finish the taskin their lesson, the teacher hope the student can coorperate in their group, But the student usually hope too in their other friends. One of learning model that can solve this problem with use cooperative scramble learning model. This Research is to knowthat using cooperative scramble learning model can give resul tstudy physics Bette compare using group at VIII gradein MTsS of Gantung Ciri Solok regency. Kind of Research that use quasy experiment Research with Research design is randomized control group only design. Population in this Research is all of student at VIII gradein MTsS of Gantung Ciri Solok regency 2016/2017. Technique of sampel interpretation that us ein this Research total sampling. The technique that use to examinehy potheses is with use similarity on average on direction pass test-t, Because distibute data normal and data group varian tthat homo gene ous. The result data analysis affective aspect, the student experiment class with average value 84,67control class and 76,28. The result data analysis cognitive aspect the student experiment class with average value = 81,87 and control class Â = 70,8. The student that get value above completeness in the experiment class is 24 person (80%) and control class is 12 person (40%). Based on test-t on real standard 0,05 gettcount=5,68 andttable=1,67, becausegettcount>ttable(5,68 > 1,67), so, it decision Ho refusedand Hi accapted. It proved the using of cooperative scramble learning model give result physics study Better than using of learning model group discussionin MTsS of Gantung Ciri Solok Regency.